The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.5194/egusphere-2023-303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coupled hydrological and hydrodynamic modelling application for climate change impact assessment in the Nemunas River watershed–Curonian Lagoon–south-eastern Baltic Sea continuum

Abstract: Abstract. We analyse the cumulative impacts of climate change in a complex basin-lagoon-sea system continuum, which covers the Nemunas River basin, Curonian Lagoon, and the south-eastern part of the Baltic Sea. A unique state-of-the-art coupled modelling system, consisting of hydrological and hydrodynamic models, has been developed and used for this purpose. Results of four regional downscaled models from the Rossby Centre high-resolution regional atmospheric climate model have been bias-corrected using in sit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Sea surface temperatures were projected to increase by 1–5 °C and salinity to decrease with up to 2.2 g kg −1 over the next 30–60 years in the three scenarios. Similar results for temperature and salinity were found for the shallow Curonian Lagoon influenced by large river discharges and low water exchange with the Baltic Sea [ 79 ]. Model projections of the Baltic Sea and North Sea likewise showed a sea water warming of 2–5 °C by the end of 2100 [ 80 , 81 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Sea surface temperatures were projected to increase by 1–5 °C and salinity to decrease with up to 2.2 g kg −1 over the next 30–60 years in the three scenarios. Similar results for temperature and salinity were found for the shallow Curonian Lagoon influenced by large river discharges and low water exchange with the Baltic Sea [ 79 ]. Model projections of the Baltic Sea and North Sea likewise showed a sea water warming of 2–5 °C by the end of 2100 [ 80 , 81 ].…”
Section: Discussionsupporting
confidence: 81%
“…Relay of suspended mussels onto the seafloor as artificial mussel beds is a new production mode, but it is not clear to what extent this will expand to support the future fishery. Previous studies have shown that system responses to climate change are more variable in coastal systems than for open waters due to the more complex geomorphology and influence by freshwater sources [ 5 , 40 , 79 ]. Hence, localized model set-ups and scenarios are needed for coastal ecosystems to achieve more realistic outcomes with higher relevance for the local community.…”
Section: Discussionmentioning
confidence: 99%